Protective Effect of N-Acetylcysteine Amide on Blast-Induced Increase in Intracranial Pressure in Rats - Kawoos, Usmah; McCarron, Richard M.; Chavko, Mikulas (Frontiers in Neurology, 2017)
Blast-induced traumatic brain injury (bTBI) is associated with acute and possibly chronic elevation of intracranial pressure (ICP). The outcome after TBI is dependent on the progression of complex processes which are mediated by oxidative stress. So far no effective pharmacological protection against TBI exists. In this study, rats were exposed to a single or repetitive blast overpressure (BOP) at moderate intensities of 72 or 110 kPa in a compressed air-driven shock tube. The degree and duration of the increase in ICP was proportional to the intensity and frequency of the blast exposure(s). In most cases, a single dose of antioxidant N-acetylcysteine amide, NACA (500 mg/kg) administered intravenously 2 h after exposure to BOP significantly attenuated blast-induced increase in ICP. A single dose of NACA was not effective in improving the outcome in the group of animals that were subjected to repetitive blast exposures at 110 kPa on the same day. In this group, two treatments with NACA at 2 h and 4 h post-BOP exposure resulted in significant attenuation of elevated ICP. Treatment with NACA prior to BOP exposure completely prevented the elevation of ICP. The findings indicate that oxidative stress plays an important role in blast-induced elevated ICP as treatment with NACA ameliorated ICP increase, which is frequently related to poor functional recovery after TBI.